2018
DOI: 10.1007/s00127-018-1522-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rates of self-harm among children, adolescents and young adults: a 10-year national registry study 2007–2016

Abstract: The findings indicate that the age of onset of self-harm is decreasing. Increasing rates of self-harm, along with increases in highly lethal methods, indicate that targeted interventions in key transition stages for young people are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 38 publications
5
104
1
2
Order By: Relevance
“…In Ireland, increases in ED self-harm rates between 2007 and 2016 were particularly pronounced among girls aged 10-19 [5]. Similarly, in the UK, self-harm incidence rates in GP-registered patient cohort increased only in younger teenage girls aged 13-16, with this group also having the highest rates of all age and sex groups [13].…”
Section: Interpretation and Comparison With Existing Evidencementioning
confidence: 95%
See 3 more Smart Citations
“…In Ireland, increases in ED self-harm rates between 2007 and 2016 were particularly pronounced among girls aged 10-19 [5]. Similarly, in the UK, self-harm incidence rates in GP-registered patient cohort increased only in younger teenage girls aged 13-16, with this group also having the highest rates of all age and sex groups [13].…”
Section: Interpretation and Comparison With Existing Evidencementioning
confidence: 95%
“…Rates of hospital-treated self-harm have been found to be particularly raised in adolescents compared to older age groups. Studies examining emergency department (ED) visits in Western countries (including Ireland, the US, Denmark and the UK) have found the highest rates of self-harm among girls aged between 15 and 19 years [5][6][7][8][9]. A substantial body of evidence indicates that economic recession and its aftermath is associated with increases in rates of suicide and self-harm, though much of this work focuses on the working-age population [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most other studies, NSSH was amalgamated with suicide attempts. [6][7][8][9] Analyses of Danish hospital registration data for 1994-2011, for example, showed a rising frequency of self-harm (with and without suicidal intent) in both sexes, with the greatest increases in women and girls aged 15-24 years. 9 Data from the National Self-Harm Registry in Ireland showed that the frequency of selfharm increased by 22% between 2007 and 2016 in 10-24-year-olds, and by more in women and girls.…”
Section: Introductionmentioning
confidence: 99%